KEDUDUKAN PANCASILA DALAM PEMBENTUKAN PERUNDANG-UNDANGAN DI INDONESIA: TINJAUAN FILSAFAT HUKUM - Muzwar Irawan; Maltus Hutagalung (Universitas Sari Mutiara Indonesia, 2026)
Indonesia, as a state based on the rule of law (rechtsstaat), places Pancasila at the center of its role as a reflective basis and philosophical foundation for the formation of legislation. Pancasila serves not only as a formal normative basis but also as a manifestation of transcendental, moral, and ethical values ​​that exist within society, as affirmed in Law Number 12 of 2011, which positions it as the source of all sources of state law. Within this framework, the exercise of state power is required to actualize the balance between legal certainty, justice, and social benefit as fundamental principles of legal creation. In line with the principle of ubi societas, ibi ius, regulatory formation is understood as a dynamic process that must be responsive to social developments. Ignoring the philosophical dimension in the formation of legislation has the potential to produce positivistic-formalistic legal products, thus distancing the law from its primary goal, namely the realization of substantive justice in the life of the nation and state